2020
DOI: 10.1039/d0ra05825d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cationic proteoliposomes using cell-free membrane protein synthesis: the chaperoning effect of cationic liposomes

Abstract: The preparation method of cationic proteoliposomes is established using a cell-free membrane protein synthesis in the presence of cationic liposomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Classically, LPs do not contain any proteins in the lipid bilayer or intraluminal space. However, different studies attempted to design proteoliposomes (proteo-LPs) that incorporate proteins [ 51 , 52 , 53 ]. Proteo-LPs have been employed as tools for studying lipid-protein and protein-protein interactions as well as topological features of different membrane-associated proteins [ 54 ].…”
Section: Structure and Composition Of Liposomes And Extracellular Ves...mentioning
confidence: 99%
“…Classically, LPs do not contain any proteins in the lipid bilayer or intraluminal space. However, different studies attempted to design proteoliposomes (proteo-LPs) that incorporate proteins [ 51 , 52 , 53 ]. Proteo-LPs have been employed as tools for studying lipid-protein and protein-protein interactions as well as topological features of different membrane-associated proteins [ 54 ].…”
Section: Structure and Composition Of Liposomes And Extracellular Ves...mentioning
confidence: 99%
“…[54] It has been reported that membrane proteins are incorporated into liposome membranes by PUREsystem expression in the presence of liposomes. [27,55] In this section, membrane protein expression was performed in the presence of lipid membrane-coated particles, and the function of the membrane proteins incorporated into the surface of the particles was investigated. The Spike protein (S protein) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was selected as the membrane protein in this study.…”
Section: Functionalization Of Lipid Membrane-coated Nanoparticles Wit...mentioning
confidence: 99%
“…[ 26 ] In addition, it has been shown that modification of proteins and other biomolecules on the membrane surface can lead to the development of smart drug delivery system (DDS) carriers with bioinspired functions. [ 27 ] However, owing to their low in vivo stability and low efficiency of drug incorporation into the inner water layer, there are still challenges in developing a highly efficient DDS using lipid bilayer membranes. [ 28,29 ] To overcome these problems, materials have been developed with the lipid membrane as a coating on the surface of core nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hybrid vesicles containing PEG modifications have an increased uptake efficiency compared to unmodified EVs. With regard to constructing hybrid EVs using liposomes to incorporate viral fusogenic proteins that induce fusion under acidic conditions, it is possible to reconstitute functional membrane proteins into liposomes in one step by cell-free protein synthesis [ 161 , 162 , 163 ].…”
Section: Drug Delivery System By Extracellular Vesiclementioning
confidence: 99%